OP0132 Myositis and pregnancy. (1st June 2001) - Silva, CA; Isenberg, DA
Abstract : Background: Polymyositis and dermatomyositis are the most common form of idiopathic inflammatory myopathy, overall the female to male ratio is 2–3: 1. The age at presentation is most often between 40 and 60 years. Pregnancies in these patients are uncommon, and the overall maternal and foetal risks are not well defined in patients with myositis. Objectives: We assessed the prevalence and outcome of pregnancy in 37 patients with dermatomyositis and polymyositis. Methods: 54 patients with myositis have been treated between 1976 and 2000 at the Bloomsbury Rheumatology Unit, University College/Middlesex Hospital. A prospective record of all such patients had been kept by one of us (DAI). All patients meet the Bohan and Peter Criteria for DM and PM. The presence of another autoimmune disease was noted as appropriate. Patients were reviewed on a regular basis in a specialist outpatient clinic, and for all patients basic demographic data, age at onset, treatment, number of pregnancies, activity of the disease during pregnancy were noted. For the purposes of this study all of the available 37 patients were examined by one of us (CS): 28 females and 9 males. Results: The female patients medium age was 44 years, with age at onset ranging from 16 to 64. 16 have Dermatomyositis/Polymyositis (7- PM/9- DM) and 12 have myositis as part of an overlap syndrome (SLE (7 patients), 2 patients with RA, 2 with SS, and 2 with Scl). Only 3 of our patients have been pregnant after the onset of the disease. One, with a poor control of her disease, had an abortion during the first trimester, and was also on treatment with MTX. The other two had the disease under control and 2 normal pregnancies with good foetal outcome was achieved. Both suspended immunosupressants during pregnancy and were able to decrease steroid dosage, without increasing disease activity. Conclusion: Pregnancy in myositis patients is a rare event. Pregnancies occuring in myositis patients with the disease under clinical remission can result in good foetal outcome. The activity of the disease remains stable. These results are consistent with the literature from recent years, and are probable due to better control of disease activity.